Perceived status and care practices among complete denture wearers - Neeraj Sharma; Jyotsna Shukla; Dheeraj Sharma; Divya Mehta; Lalita Kakde; Krati Bais (Wolters Kluwer Medknow Publications, 2020)
Background: Oral health is neglected even today. This can be evidently seen in the low utilization rates and poor oral health status. Conventional dentures are the most common treatment option in the restoration of lost teeth. Without appropriate denture care practices, there is an elevated risk of developing a multitude of problems. The aim of this study was to assess the perceived status and care practices among complete denture wearers in Modern Dental College and Research Centre, Indore, Madhya Pradesh, India. Materials and Methods: A cross-sectional study was conducted in the Department of Prosthodontics at the Modern Dental College and Research Centre, Indore, Madhya Pradesh, India. Patients with self-care optimum overall health who were using either single or full complete dentures for more than 1 year from the commencement of the study were requested to participate in the study. A total of 1000 study participants were given a self-administered questionnaire on their denture care practices followed by clinical examination of the denture status. Data were statistically analyzed using the Statistical Package for the Social Sciences software for Windows, version 20.0. Results: Maximum denture wearers informed that they cleaned their dentures once a day, with brush and water, and had the habit of removing the dentures before sleeping at night. Almost 90% of the participants reported their denture status to be good or fair. Clinical examination revealed that slightly more than half of the participants had poor denture status. Conclusion: This study signifies the importance for improvement in patient oral health education and counseling with respect to the maintenance of dentures and upkeep of denture hygiene. It also emphasizes the need for educating patients on how to evaluate the status of their dentures.